Plasma Fibrinogen and sP-Selectin are associated with the risk of lung cancer in a prospective study - Grafetstätter, Mirja; Johnson, Theron S.; Pletsch-Borba, Laura; Katzke, Verena; Hoffmeister, Michael; Bugert, Peter; Kaaks, Rudolf; Kühn, Tilman (Cancer epidemiology, biomarkers & prevention, 2019)
Background: While enhanced platelet activation and a procoagulant state may drive lung cancer progression and metastases, less is known about their role in earlier phases of cancer development. Thus, we evaluated whether prediagnostic biomarkers of platelet activation and coagulation are related to the risk of lung cancer in the prospective EPIC-Heidelberg Study using a case-cohort design. - Methods: Levels of fibrinogen, soluble glycoprotein (sGP) IIb/IIIa, soluble P-selectin (sP-selectin), soluble thrombomodulin (sTM), and thrombopoietin (TPO) were measured in baseline plasma samples of a random subcohort (n = 2,480) and incident cases of lung cancer (n = 190). Multivariable-adjusted Cox proportional hazards regression analyses were used to obtain HRs of lung cancer across quartiles of biomarker levels. - Results: Fibrinogen [HR highest vs. lowest quartile: 1.91 (95% confidence interval: 1.09-3.34)] and sP-Selectin [HR: 2.51 (1.39-4.52)] were significantly associated with lung cancer risk in multivariable adjusted Cox regression models. Adding both biomarkers to the established PLCOm2012 algorithm, which alone showed a C-statistic of 0.788, led to a slight increment in lung cancer risk prediction, with a C-statistic of 0.814. - Conclusion: Our findings indicate that enhanced platelet activation and a procoagulative state contribute to lung carcinogenesis. - Impact: The current prospective study supports the hypothesis of increased coagulation being a possible driver of lung carcinogenesis, as strong positive associations were found between two procoagulative markers, sP-Selectin and fibrinogen, with lung cancer risk. Both biomarkers could improve lung cancer risk prediction, but external validation of the results is needed.